ChemInform Abstract: Cephalofortunone, a Structurally Unique Cephalotaxus Alkaloid from Cephalotaxus fortune Hook. f. Issue 7 (January 2016) - Li, Hanxiang; Wen, Yanhua; Wang, Feifei; Wu, Ping; Wei, Xiaoyi
Abstract: isolation and structure elucidation